2017
DOI: 10.1002/ccd.26978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coronary dominance on 2‐year outcomes after percutaneous coronary intervention in patients with acute coronary syndrome

Abstract: LD was an independent predictor of long-term mortality in ACS patients undergoing PCI. The effect of LD still existed after adjustment for several important variables and was independent of SYNTAX score. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…13 Multiple other studies have reported significant role of left dominance in determining the short and long term fate of patients with STE-ACS. In a study by He C et al 10 , left dominance was reported to be an independent predictor of long-term mortality with 2-year mortality rate of 2.58% against 1.23% mortality in right or codominance (p=0.024). Parikh NI et al 14 in a large registry based study confers the modestly increase in in-hospital mortality after PCI of ACS patients with left dominant system.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…13 Multiple other studies have reported significant role of left dominance in determining the short and long term fate of patients with STE-ACS. In a study by He C et al 10 , left dominance was reported to be an independent predictor of long-term mortality with 2-year mortality rate of 2.58% against 1.23% mortality in right or codominance (p=0.024). Parikh NI et al 14 in a large registry based study confers the modestly increase in in-hospital mortality after PCI of ACS patients with left dominant system.…”
Section: Discussionmentioning
confidence: 95%
“…Although, the left dominant circulation system is considered a normal entity but its prognostic role has been hypothesized mainly due to unbalanced supply of blood to the cardiac muscle. 10,11 Therefore, we conducted this study to evaluate the role of left dominant circulation system in determining the fate of STE-ACS patients with culprit proximal LAD. It has been observed that, in this particular sub-groups of STE-ACS patients, the clinical manifestation, risk factor distribution, most of the angiographic findings, and hospital course were not different between the left and right dominant groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were divided into two groups (LD and RD+CD) based on coronary angiographic images using standard angiographic projections in accordance with the American College of Cardiology/American Heart Association College. RD and CD patients were in the same group because they had been previously reported with similar anatomical and clinical features [4,5] . Moreover, it was not possible to precisely distinguish between CD and RD patients due to diffuse coronary lesions.…”
Section: Study Population and Data Sourcementioning
confidence: 99%
“…However, the differences between coronary dominance types may lead to different clinical outcomes in patients with coronary artery stenosis according to various studies [3] . Left coronary dominance has been shown to be a poor prognostic factor in patients with acute coronary syndrome (ACS) and percutaneous interventions [4,5] . In contrast, the knowledge about the clinical effects of the type of coronary dominance is scarce in patients undergoing surgical revascularization.…”
Section: Introductionmentioning
confidence: 99%